1992
DOI: 10.1042/bj2840457
|View full text |Cite
|
Sign up to set email alerts
|

The lipolysis/esterification cycle of hepatic triacylglycerol. Its role in the secretion of very-low-density lipoprotein and its response to hormones and sulphonylureas

Abstract: In hepatocyte cultures maintained in the absence of extracellular fatty acids, at least 70 % of the secreted very-low-density lipoprotein (VLDL) triacylglycerol was derived via lipolysis of intracellular triacylglycerol. This proportion was unchanged when the cells were exposed for 24 h to insulin or glucagon, hormones which decreased the overall secretion of intracellular triacylglycerol, or to chloroquine or tolbutamide, agents which inhibit lysosomal lipolysis. The rate of intracellular lipolysis was 2-3-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
217
1
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(235 citation statements)
references
References 35 publications
16
217
1
1
Order By: Relevance
“…isolated hepatocytes [123] and in i o [124] that only a minor proportion of the flux leading from cytosolic TAG to secreted TAG is due to transfer en bloc of intact molecules of TAG. Rather, the cytosolic TAG has to undergo a degree of hydrolysis and re-esterification before being utilized for secretion.…”
Section: Figure 3 Schematic Representation Of the Possible Inter-relamentioning
confidence: 98%
See 1 more Smart Citation
“…isolated hepatocytes [123] and in i o [124] that only a minor proportion of the flux leading from cytosolic TAG to secreted TAG is due to transfer en bloc of intact molecules of TAG. Rather, the cytosolic TAG has to undergo a degree of hydrolysis and re-esterification before being utilized for secretion.…”
Section: Figure 3 Schematic Representation Of the Possible Inter-relamentioning
confidence: 98%
“…The scheme is based on proposals by several authors (see [120][121][122][123][124][125]). Further abbreviations : MAG, monoacylglycerol ; PC, phosphatidylcholine ; PE, phosphatidylethanolamine.…”
Section: Figure 3 Schematic Representation Of the Possible Inter-relamentioning
confidence: 99%
“…Since the physiological role of the microsomal CATs is not yet known it is not possible to tell whether any of the various documented extrapancreatic effects of the sulphonylureas could result from interactions with microsomal CATs. We are however struck by the facts that 5 mM tolbutamide inhibited VLDL secretion by rat hepatocytes by 75% [8] and (at physiological carnitine concentrations) also inhibited the liver microsomal malonyl-CoA-sensitive CAT by 75% (Fig. 1).…”
Section: Analysis Of Datamentioning
confidence: 99%
“…The effect of tolbutamide on the malonyl-CoA-inhibitable transferase was influenced by the phospholipid/detergent environment whereas the effect of glibenclamide was not. Key words: Carnitine acyltransferases; Glibenclamide; Liver; Microsome; Sulphonylureas; Tolbutamide Wiggins and Gibbons [8] have shown that the sulphonylurea drug tolbutamide is able to suppress VLDL triacylglycerol secretion by hepatocytes. Tolbutamide appeared to have two actions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation